Factors that contribute to the workplace accidents in manufacturing industries: a case study in Ajiya Safety Glass Sdn. Bhd. at Segamat, Johor / Nurulain Azman and Intan Nurnadia Mohd Nor - Azman, Nurulain; Mohd Nor, Intan Nurnadia (Faculty of Administrative Science and Policy Studies, 2014)
This chapter provides the background of study, the problem statement, research objectives and research questions of the study. Moreover, in this chapter the significant and scope of study is also presented. Lastly, at the end of this chapter the definitions of key terms are also provided.